ANALYSIS OF CHALLENGES AND STRATEGIES FOR HISTORY TEACHERS IN INTEGRATING INFORMATION TECHNOLOGY TO SUPPORT LEARNING AT SMAN 14 MEDAN - Silaban, Arifin; Diansyah, Arfan; Gultom, Imelda Megawati (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2024)
This research aims to analyze the challenges faced by history teachers in integrating information technology into the history teaching process, as well as identify effective strategies to overcome these challenges. The research method used is interviews and observations of a number of history teachers who have actively used information technology in their teaching. The research results show that some of the main challenges faced by history teachers include limited access to technology, uncertainty in selecting appropriate digital content, and a lack of adequate training in the application of technology. However, the research also identified several effective strategies that history teachers have used to overcome these challenges, including ongoing training and professional development, collaboration between teachers to share resources and experiences, and adapting curricula to account for technology integration. The implication of this research is the need for greater support from schools and the government in providing adequate access to technology and contextual training for history teachers so that they can effectively integrate information technology into history learning. The implementation of the strategies adopted by history teachers at SMA 14 shows their commitment to overcoming the challenges of integrating technology in history learning. In the face of limited access to technology, teachers have been active in utilizing training and professional development to improve their skills in using technology. Collaboration between teachers also provides a platform for sharing experiences and ideas for facing common challenges. Curriculum adjustments are the main basis for ensuring that history learning remains relevant and interesting for students in this digital era. By utilizing technology in lesson plans and developing interactive learning materials, teachers have created a dynamic and student-oriented learning environment. The impact of this strategy can be seen in increasing students' understanding of historical material and their skills in using technology.